Cerebral localization of higher functions: The period between Thomas Willis and Paul Broca - Engelhardt, Eliasz (Dement Neuropsychol, 2019)
The age-old debates about the localization of the mind (higher functions) took a new course when Willis located a higher nervous function (memory) in the brain parenchyma, and supposedly, in the cerebral cortex. About two centuries later, Broca, founded on solid scientific reasoning, localized a circumscribed area of the 3(rd) frontal circumvolution of the left hemisphere as the seat of articulate language, a higher function (speech - language domain). He (and Dax) also defined the functional asymmetry (specialization) of the hemispheres, with left dominance (for language). The period between the findings of these individuals was not quiescent, as numerous authors contributed with their theoretical and clinicopathological research toward creating a conducive scientific atmosphere for this accomplishment, and should be regarded as important. Further studies, in the decades that followed, revealed the localization of additional aspects of language and of other higher functions (cognitive domains).